DYNAMICS OF ROLES IN THE TRADITION OF HUMMING IN THE MIDST OF SOCIAL CHANGE IN PAKPAK SOCIETY - Muhammad Rifai; Lister Berutu; Tri Presar Jhon Tuan Panjaitan; Maulida Masyitoh; Tresno Tresno (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
The traditional ceremony of mengerumbang is one of the important traditional rites in Pakpak society, carried out by elderly individuals as a form of repayment of traditional debts to hula-hula before death. This study aims to examine the symbolic meaning, social structure, and socio-cultural function of the mengerumbang ceremony in the context of contemporary Pakpak society and to observe the role of this tradition. The research method uses a qualitative approach with ethnographic methods through participatory observation, in-depth interviews with traditional leaders and ritual practitioners, and documentary studies of local customs and practices. The results of the study show that mengerumbang is not merely a customary ritual, but a social mechanism to maintain the honour of individuals and families, strengthen the continuity of the sulang silima kinship system, support economic redistribution through customary gifts, and legitimise a person's social status within the Pakpak customary structure. Furthermore, changes in ritual practices due to the influence of religion and modernisation indicate a dynamic process of cultural adaptation without eliminating the core meaning of the custom. Thus, mengerumbang functions as a space for negotiation between tradition, identity, and social change in Pakpak society.